“I trust the cosmos” - interview with Kidlat Tahimik - Hering, Tobias; Baumgartel, Tilman (2019)
Access online through this link:https://www.plarideljournal.org/article/i-trust-the-cosmos-interview-with-kidlat-tahimik
Keywords: Kidlat Tahimik -- Interviews; Filmmakers